Ability of ketapang leaf (Terminalia cattapa) in reducing the content of heavy metals copper (Cu) in the water - Islamiah Islamiah; Umroh Umroh; Eva Prasetiyono (Journal of Aquatropica Asia, 2016)
Activities of tin mining in Bangka Belitung resulted in the formation of water contained-pit called Kulong that contains heavy metals copper (Cu). Copper is a heavy metal that is needed by organisms, but at higher concentrations will have a negative impact for the organisms. The compound contained in the biomass of Ketapang leaf (Terminalia cattapa) has the potential to reduce the concentration of copper in water. The purpose of this study was to know the capabilities and the best dosage of ketapang leaf in decreasing the concentration of copper in water. The experimental design used was Completely Randomized Design with 4 treatments and 3 replications per treatment. The results show that the leaf of ketapang has the ability to absorb the copper in the water with the best dosage was 5 g/L